PERAN DPD DAN GAGASAN AMANDEMEN KELIMA UUD 1945 - Nuruddin Hady (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2012)
Regional Representatives Council(DPD) is astate agency subject to the provisions ofArticle22 and Article 22DC 1945 Amendment. This institute is a substitute of regional representatives and group representatives as we have ever known before. Various parties think that DPD authority by are still weak and as if only as a subordinate staff of experts with the Iouse. This lead to the idea of thenecessity of returning to the 1945 Constitution amendments, particularly with respect to the authority to strengthen the authority of the Council. DFD has a huge role to accommodate the aspirations of the region associated with the implementation of regional autonomy, both in terms of financial management sourced from the General Allocation Fund, as weil as the poteirtial of natural resources in the region, spatial, poverty, natural disasters, health, environmentand others. While the Council has not and is not even sensitive to the issues that come into direct contact with development interests and welfare of local communities. The idea of the Fifth Amendment must be seriously considered and studied, since amendments to the constitutionis a necessity. The idea of the needfor further amendments to the 1945 Constitution should be appreciated by first preparing a clear grand design ofthe material constitutionneeds tn be amended. Therefore, the amendmentis not just a patch work. And the most urgent one is that pecple candirectly take benefit from the amendment.